2014 IEEE Eighth International Conference on Research Challenges in Information Science (RCIS) 2014
DOI: 10.1109/rcis.2014.6861072
|View full text |Cite
|
Sign up to set email alerts
|

The four pillars of crowdsourcing: A reference model

Abstract: Abstract-Crowdsourcing is an emerging business model where tasks are accomplished by the general public; the crowd. Crowdsourcing has been used in a variety of disciplines, including information systems development, marketing and operationalization. It has been shown to be a successful model in recommendation systems, multimedia design and evaluation, database design, and search engine evaluation. Despite the increasing academic and industrial interest in crowdsourcing, there is still a high degree of diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 70 publications
(51 reference statements)
0
107
0
3
Order By: Relevance
“…Table 1 Selected crowdsourcing projects classified by service and innovation purpose Furthermore, from our review, crowdsourcing and its outcomes vary in terms of who, why, how, and what, thus this paper adopts a simple framework, displayed in figure 1, elaborating on these key components by focusing on crowds, motivation, process design, and outcomes. These categories are developed through reviewing extant frameworks and review articles on crowdsourcing in different fields (e.g., Albors, Ramos, and Hervas 2008; Malone, Laubacher, and Dellarocas 2010;Brabham, 2013;Hosseini et al 2014). This framework provides a structure for exploring the existing research about crowdsourcing across disciplines but is not intended to convey relationships and direction among the categories.…”
Section: What Is Crowdsourcing?mentioning
confidence: 99%
“…Table 1 Selected crowdsourcing projects classified by service and innovation purpose Furthermore, from our review, crowdsourcing and its outcomes vary in terms of who, why, how, and what, thus this paper adopts a simple framework, displayed in figure 1, elaborating on these key components by focusing on crowds, motivation, process design, and outcomes. These categories are developed through reviewing extant frameworks and review articles on crowdsourcing in different fields (e.g., Albors, Ramos, and Hervas 2008; Malone, Laubacher, and Dellarocas 2010;Brabham, 2013;Hosseini et al 2014). This framework provides a structure for exploring the existing research about crowdsourcing across disciplines but is not intended to convey relationships and direction among the categories.…”
Section: What Is Crowdsourcing?mentioning
confidence: 99%
“…The geospatial information added is in the form of longitude and latitude [14]. The purpose of the process is so that the object (media) can be positioned exactly to the coordinates on a map [15].…”
Section: Geotaggingmentioning
confidence: 99%
“…A study [18] found that there is a deviation in the literature on what should be essential and optional for a crowdsourcing technique. For example, competency of the crowd in doing a task is a core [19] but it is not necessary in other case [20].…”
Section: Crowdsource Reference Modelmentioning
confidence: 99%
“…In this paper, we discussed a crowdsource reference model [18] and analyzed how it is can be utilized for the understanding of mobile app reviews as a crowdsourcing technique. We have discussed each construct of the reference model from the perspective of mobile app reviews and analyzed whether specific features of the crowdsource reference model are applicable in our case or not.…”
Section: Introductionmentioning
confidence: 99%